Isolasi, Identifikasi, Karakterisasi, dan Uji antibiofilm Derivat Asam Galat dari Kulit Batang Sterculia quadrifida R.Br - Rollando, Rollando (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Faloak (Sterculia quadrifida R.Br) is used empirically by residents of Timor island to treat hepatitis, typhoid, ulcers, and to restore stamina. Information of active compound contained in the bark of faloak specifically unpublished. This study aims to determine the active compound contained in faloak bark that can be used as antibiofilm. The extraction was performed by soxletation method, the isolation was performed by gradien isolation method, the elusidation was performed by merging information from NMR and LC-MS spectra analysis. The biofilm inhibition activity test was performed by microdilution method formed on flat bottom flexible microplate U-bottom PVC 96 wells with staining using 1% crystal violet. The isolation process obtained 3 gallic acid derivatives, named isolate 1, isolate 2, and isolate 3. Test of inhibition of biofilm formation showed isolate 1 has IC50 of 46,87 µg/mL, isolate 2 has IC50 of 45,87 µg/mL, and isolate 3 has IC50 42,65 µg/mL.The biofilm test results showed that isolates 1-3 had high biofilm inhibition potency.